Teachers' participative management and its relationship with job satisfaction : a study on teachers teaching at Darussalam Modern Islamic Boarding School, East Java, Indonesia - Ishak, Fajeri (Institute of Education, International Islamic University Malaysia, 2013)
The main objective of this study is to examine the correlation between participative management and teachers' job satisfaction at Darussalam Modern Islamic Boarding School, Ponorogo, East Java, Indonesia. Furthermore, it tries to identify the significant differences among teachers of different genders and with different years of teaching experience on their perceptions of participative management. Finally, the study attempts to investigate the level of teachers' (both male and female) participation regarding the three elements of participative management namely, defining and clarifying tasks and duties, sharing of information, and being involved in work related issues and job satisfaction. For these purposes, a questionnaire was specifically designed to get information from the respondents who were teachers of the school. To describe the respondents' perceptions regarding the level of participative management and job satisfaction, descriptive analysis was used in this study. A questionnaire, using the Five-Point Likert Scale, was employed as an instrument to collect data. The sample of the study was randomly selected. It consisted of 222 teachers at the school. Frequencies, percentages, means, and standard deviations for each item of the questionnaire were computed. The independent sample t-test shows that there is significant difference between males and females regarding the implementation of participative management. However, one-way analysis of variance (ANOVA) shows a different result. It shows that there was no statistically significant difference among teachers with different years of experience on the implementation of participative management. On one hand, the analysis reveals a high level of participative management based on teachers' perception. Similarly, the study also found that the degree of job satisfaction among teachers was at a high level. On the other hand, this study indicates that a positive correlation does not occur between factors of participative management and job satisfaction except in sharing of information factor. In summary, the study shows that overall teachers' participative management has no significant relationship with teachers' job satisfaction at the school. Finally, the study provides recommendations to the Head of Darussalam Modern Islamic School on how to improve the participation and job satisfaction among teachers.